TRANSFORMATIONAL LEADERSHIP, TRAINING, DAN EMPLOYEE PERFORMANCE: MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN JOB SATISFACTION - Didit Haryadi; Wawan Prahiawan; Hayati Nupus; W Wahyudi (Universitas Multimedia Nusantara, 2021)
Abstract-The purpose of this study is to examine and analyze in improving employee performance with transformational leadership and appropriate training through organizational citizenship behavior and job satisfaction to mediate improving employee performance. This study uses a descriptive quantitative method with a causal approach. The object of this research at PT. Nikomas Gemilang Serang Chemical Rubber Division of Nike Hottptress Section used a sample of 160 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. The data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Transformational leadership has a positive and significant effect on employee performance. 2). Training has a positive and significant effect on employee performance. 3). Transformational leadership has a significant effect on organizational citizenship behavior. 4). Training has a positive and significant effect on organizational citizenship behavior. 5). Organizational citizenship behavior has a positive and significant effect on employee performance. 6). Training has a positive and significant effect on job satisfaction. 7). Job satisfaction has a positive and significant effect on employee performance. Organizational citizenship behavior and job satisfaction can mediate between transformational leadership and training on employee performance. Keywords: Employee Performance; Job Satisfaction; Organizational Citizenship Behavior; Training; Transformational Leadership